2005
DOI: 10.1073/pnas.0409888102
|View full text |Cite
|
Sign up to set email alerts
|

CB 2 cannabinoid receptor activation produces antinociception by stimulating peripheral release of endogenous opioids

Abstract: CB2 cannabinoid receptor-selective agonists are promising candidates for the treatment of pain. CB2 receptor activation inhibits acute, inflammatory, and neuropathic pain responses but does not cause central nervous system (CNS) effects, consistent with the lack of CB2 receptors in the normal CNS. To date, there has been virtually no information regarding the mechanism of CB2 receptormediated inhibition of pain responses. Here, we test the hypothesis that CB2 receptor activation stimulates release from keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
436
1
14

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 477 publications
(466 citation statements)
references
References 31 publications
15
436
1
14
Order By: Relevance
“…CBr2 on keratinocytes mediates antinociception via opioid release. [17,18] CBr2 stimulates β-endorphin release from keratinocytes, leading to antinociception through μ-opioid receptors. We therefore investigated a CBr2 selective agonist in the mouse cancer pain model.…”
Section: Discussionmentioning
confidence: 99%
“…CBr2 on keratinocytes mediates antinociception via opioid release. [17,18] CBr2 stimulates β-endorphin release from keratinocytes, leading to antinociception through μ-opioid receptors. We therefore investigated a CBr2 selective agonist in the mouse cancer pain model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore one of them, HU-308 [102], does not produce hypothermia, catalepsy, or behavioural changes, while the role of CB 2 receptors is fundamental in other cannabimimetic actions, such as immunomodulatory and antiproliferative effects. On the other hand, as mentioned earlier, new CB 2 receptor properties are being discovered, as it has been confirmed that they indirectly stimulate opioid receptors located in primary afferent pathways [67].…”
Section: Therapeutic Uses Of Cannabinoids In Pain Episodesmentioning
confidence: 80%
“…Structurally they consist of seven folded transmembrane helices with intra-and extracellular loops, functionally involved in signal transduction. The CB 2 receptor is located mainly in the immune system, but has been found in others sites, as in keratinocytes [67]. On the other hand, the CB 1 receptor, which is the cannabinoid receptor that has been most studied, has high levels in brain but also lower levels in spinal and peripheral nervous tissue (including areas important for pain perception, as will be discussed below).…”
Section: Endogenous Cannabinoid System Endogenous Cannabinoid Receptorsmentioning
confidence: 99%
See 2 more Smart Citations